The potential of targeting Wnt/β-catenin in colon cancer. (June 2014) - Sebio, Ana; Kahn, Michael; Lenz, Heinz-Josef
<x xml:space="preserve">Abstract</x> The Wnt signaling pathway controls several cell processes, such as motility and proliferation during embryonic development. Wnt signaling is also involved in the maintenance of potency and the induction of differentiation in stem cells. Aberrant Wnt signaling is implicated in several cancer types. Particularly in colorectal cancer (CRC), the Wnt-β-catenin signaling cascade is at the center of the carcinogenesis, and mutations in this pathway can be found in almost all CRC patients. We discuss the potential of targeting Wnt-β-catenin signaling with a brief overview of the pathway and the most promising pathway inhibitors.